Social interaction within the village migrant circular pins town of Banda Aceh, Indonesia - Rusli Yusuf (Syiah Kuala University, 2013)
The research was conducted in Peuniti Banda Aceh, with the objective of identifying and assessing the realization of social integration and social conflicts that occurred among migrants, and among migrant populations